ANALYSIS INVESTMENT OPPORTUNITIES OF UZBEKISTAN IN TOURISM SPHERE - Komilova Sarvinoz Qayumjon qizi (Central Asian Journal of Theoretical and Applied Science, 2022)
The paper aims to give some insights into the investment environment and the analyses of factors influencing. The study is motivated by the high failure rate of foreign investments in Uzbekistan. The findings of the study will benefit both local investors who are interested in learning about contemporary methods of investment valuation and foreign investors who are interested in assessing investment opportunities in Uzbekistan. The complexities of evolution of investment opportunities in emerging markets have been studied before. The problems associated with transparency, foreign exchange volatility and liquidity, contagion, governance, political risks (Note 1), and corruption have differing impacts on pricing and valuation across countries and regions. Uzbekistan is a newly-independent Central Asian country, where the same approaches of valuation methods are employed as in Russia, the Ukraine, and other European parts of the former Soviet Union. The provided analysis of investment climate in Uzbekistan suggests that the currency convertibility, lack of transparency and predictability, overregulated financial sector, limiting ownership and restrictions in “strategic” sectors are the greatest obstacles for many potential foreign investors. Also, inadequacies in investment policy and underdevelopment of stock exchange resulted 60% of all foreign investments went to energy sector.  Despite the fact that the government has a complex of laws, aimed at attracting greater foreign investment into the country based on the regulation of investment activity, foreign investors still experience substantial difficulties due to variances in enforcement and interpretation of these laws. This article offers a comprehensive overview of challenges of attracting foreign investment into Uzbekistan.